TemuKita: Web-Based Accessible Tourism Recommendation System with Disability Profile Personalization - Ricky Rohmanto; Nandika Aditia (Journal of Applied Information System and Informatic (JAISI), 2026)
The development of inclusive tourism in Indonesia faces significant challenges, particularly in providing accessible information for people with disabilities. Existing travel platforms rarely accommodate the specific needs of users with physical, visual, hearing, or intellectual disabilities, resulting in limited access to tourism destinations and services. This study aims to design and implement TemuKita, a web-based accessible tourism recommendation system that personalizes destination suggestions based on individual disability profiles. The system was developed using the Django framework with the Python programming language, PostgreSQL as the database management system, and Tailwind CSS to create a responsive mobile-first user interface that can be accessed easily from various devices. The development methodology follows the Prototype model, encompassing requirements analysis, system design, implementation, evaluation, and testing phases. TemuKita provides several key features including automatic accessibility filtering based on disability profiles, verified destination information with accessibility scores, inclusive service booking such as sign language guides and wheelchair-accessible transportation, a real-time chat system for communication between users and service providers, and a simulation-based payment system. In addition, the platform offers user reviews and recommendations to improve the reliability of accessibility information for future visitors. Black-box testing results demonstrate that all system features function correctly according to the specified requirements. The system successfully filters tourism destinations automatically based on user disability profiles, improving the relevance and accuracy of recommendations for users with disabilities. This research contributes to the development of inclusive digital tourism infrastructure in Indonesia, particularly for the Tasikmalaya region, and demonstrates the feasibility of building accessible tourism platforms using open-source technologies to support equal tourism opportunities for all users. Keywords— Accessible tourism; disability; Django framework; web-based system; recommendation system; inclusive tourism